An Overview Of The Knowledge Of Toddlers Mother About The Importance Of Immunization In Maradekaya Village, Bajeng District, Gowa Regency - Nurhijrani, Nurhijrani; Bahar, Asriani (Jurnal EduHealth, 2022)
Immunization proven as one of the most important public health efforts for reducing mortality and mobility because of various diseases could be prevented by immunization. Immunization coverage in Asia reaches 96.3% -100%. In Indonesia immunization coverage reaches 77.0% -80.0%. The aimed of this study was to find out the description of the knowledge of mothers under five about the importance of immunization in Maradekaya Village, Bajeng District, Gowa Regency in 2021.This study used a descriptive design which aimed to measure or describe the knowledge of mothers under five about immunization. Location of the research in Maradekaya village with 30 respondents. Based on the results of the knowledge indicated that in table 4.4 which was carried out on 30 respondents in Maradekaya Village, it showed that there were 7 respondents (23%) had good knowledge, while 16 respondents (54%) had less knowledge. Through this activity, it was hoped that could increase information toddlers’ mother about the importance of immunization and increased visitation to Maradekaya Village, Bajeng District, Gowa Regency.